Предмет: Алгебра, автор: Ablai97

Задания во вкладках..........

Приложения:

Ответы

Автор ответа: kalbim
0
Упростим вначале выражение:
 frac{x^{4}-1}{x+1}= frac{(x^{2}-1)(x^{2}+1)}{x+1}= frac{(x-1)(x+1)(x^{2}+1)}{x+1}=(x-1)(x^{2}+1)=x^{3}-x^{2}+x-1
Возьмем интеграл:
 intlimits^6_0 {(x^{3}-x^{2}+x-1)} , dx= frac{x^{4}}{4}-frac{x^{3}}{3}+frac{x^{2}}{2}-x=frac{6^{4}}{4}-frac{6^{3}}{3}+frac{6^{2}}{2}-6=6*(frac{6^{3}}{4}-frac{6^{2}}{3}+frac{6}{2}-1)=6*(54-12+3-1)=6*44=264
Автор ответа: Artem112
0
 intlimits^6_0 { frac{x^4-1}{x+1} } , dx = intlimits^6_0 { frac{(x-1)(x+1)(x^2+1)}{x+1} } , dx =
intlimits^6_0 {(x-1)(x^2+1)} } , dx =
\
=intlimits^6_0 {x^3-x^2+x-1} } , dx =( frac{x^4}{4} - frac{x^3}{3} + frac{x^2}{2} -x)|^6_0=
\
=( frac{6^4}{4} - frac{6^3}{3} + frac{6^2}{2}- 6)-( frac{0^4}{4} - frac{0^3}{3} + frac{0^2}{2} -0)=
324- 72 + 18- 6=264
Похожие вопросы